Lawatan Tuanku Canselor ke perpustakaan - Kekal, Abadi (Perpustakaan Universiti Malaya, 1986)
His Royal Highness The Sultan of Perak, Sultan Azlan Muhibbuddin Shah, as the third Chancellor of the University of Malaya, graced the Library by visiting us on 4 September 7986. HRH was escorted on a tour of several special exhibitions which were staged to mark this auspicious event. Four themes formed the basis of the exhibitions. On the ground floor, HRH saw the exhibition of materials on the University of Malaya; the publications of the University of Malaya Press and the Library. On the first floor was a special exhibition of the Library's holdings on the state of Perak. Another exhibition with the theme 'From manuscript to microform' showed selected exhibits from the Library's vast holdings of materials for study, teaching and research together with the specialised equipment available to assist readers with the advances in information technology. To mark the occasion, HRH was presented with a selected number of books published by the Library.